The impact of perceived character similarity and identification on moral disengagement. (22nd December 2011) - Tsay, Mina; Krakowiak, K. Maja
Enjoyment of entertainment media has often been conceptualised as a function of viewers' dispositions towards characters and the gratification sought from witnessing the justification of character actions. Motivated by disposition theory and thirdperson effect's social distance corollary, this study examines how character similarity and identification predict the degree to which viewers morally disengage, or accept antisocial behaviours of characters as morally acceptable. Findings suggest that perceived similarity between the viewer and character mediates the relationship between identification and moral disengagement, which in turn leads to greater affective enjoyment of a narrative. Implications for the nature of the moral disengagement process and its effects are discussed.